PROGRESSIF MUSCLE RELAXATION (PMR) UNTUK PASIEN HIPERTENSI - Abrar, Eva Arna; Fauzia, Liza; Sabil, Fitri A.; Anisa, Nurul Reski (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study is entitled Progressive Muscle Relaxation (PMR) for Hypertension Patients. Hypertension is a “silent killer” causing an iceberg phenomenon. The prevalence of hypertension increases with age. Hypertension is a non-communicable disease whose incidence rate is quite high. One of the therapies that can handle complaints due to hypertension is Progressive Muscle Relaxation (PMR). The purpose of the implementation of this service activity is to help relieve the muscle tension of people with hypertension. This activity was held at the tamalate health center in Makassar city involving 20 participants suffering from hypertension. The majority of respondents were female (85%), the average age was 56-65 years (60%), the majority had a high school education (85%), and the average respondent's occupation was housewife (50%). Participants participated in this activity with enthusiasm and were able to follow the relaxation movements demonstrated by the facilitator.